Antisocial Capital: Community Cohesion and Tax Avoidance among American Elites - Doron Shiffer-Sebba; Yossi Harpaz (Socius, 2024)
Studies of social capital usually emphasize its prosocial, deviance-reducing effects. This article instead explores its negative potential. The authors focus on the relationship between different forms of community-level social capital and tax avoidance by wealthy Americans, using data from the Panama Papers leaks to analyze the residential communities of Americans who engaged in offshore tax avoidance. The analysis demonstrates, first, that communities with more civic organizations are more likely to have tax avoiders. This finding suggests that civic organizations may promote cohesion among wealthy elites, producing insular attitudes and deviance. Second, income inequality correlates with tax avoidance, indicating that highly unequal communities have more insular elites. Finally, more patriotic communities have lower tax avoidance. These findings empirically establish the concept of “negative social capital” and advance the distinction between bridging (or cross-group) social capital, which lowers deviance, and bonding (or within-group) social capital, which is actually associated with greater elite deviance.